2019
DOI: 10.1177/0885066619887693
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Transesophageal Echocardiography Performed by Intensivists and Emergency Physicians in Critically Ill Patients With Coagulopathy and Thrombocytopenia: A Single-Center Experience

Abstract: Introduction: The use of transesophageal echocardiography (TEE) by intensivist physicians (IPs) and emergency physicians (EPs) in critically ill patients is increasing in the intensive care unit, emergency department, and prehospital environments. Coagulopathy and thrombocytopenia are common in critically ill patients. The risk of performing TEE in these patients is unknown. The goal of this study was to assess whether TEE is safe when performed by IPs or EPs in critically ill patients with high bleeding risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…This is consistent with other publications. 14,15 A large proportion (107 exams, 43%) of patients died within 7 days of having TEE performed. This reflects the patient acuity when TEE was performed but does limit the evaluation of complications as autopsy data unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with other publications. 14,15 A large proportion (107 exams, 43%) of patients died within 7 days of having TEE performed. This reflects the patient acuity when TEE was performed but does limit the evaluation of complications as autopsy data unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not have any cases of bleeding in this study, it is a potential concern because the coagulation status of ED patients is usually not known at the time of the F‐TEE examination. However, a recently published series of critically ill patients with coagulopathy or thrombocytopenia who underwent F‐TEE showed that these patients did not have a higher risk of bleeding after the procedure 57 . A review of the literature for esophageal perforation associated with TEE examinations found four studies including 20,000 patients, with four reported cases of esophageal perforation for a rate of 0.02% 58–61 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the usage of TEE has escalated in the emergency department (ED) and critical care, and this trend is well documented in the literature [13][14][15][16][17][18][19][20][21][22]. Focused or resuscitative TEE are terms used to describe the usage of limited TEE views to facilitate early recognition of pathologic processes and to guide clinical decision-making in critically ill patients [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Focused TEE in the ED is beneficial in the management of cardiac arrest [17,18] undifferentiated shock [19] and trauma [20,21]. The use of TEE by non-cardiologists in the ED and intensive care setting for critically ill patients is safe [22] and extremely useful in resource-limited setting [23]. However, focused TEE does not replace the need for comprehensive TEE when clinical questions exceed the scope of a limited exam.…”
Section: Introductionmentioning
confidence: 99%